Impact of sports balls with striking implements - Cross, R. (Sports Engineering, 2014)
A common problem in sports mechanics is to understand and to model the impact of a sports ball with some other object such as a sports surface or an implement used to strike the ball. In this review, we focus on a simple collision model that effectively reduces the problem to a collision between two point masses. The mass of the striking implement is replaced by its effective mass, the latter quantity depending primarily on the "swing weight" of the implement and the location of the impact point. For normal or perpendicular impacts, energy loss can be described in terms of the normal coefficient of restitution, ey , or an equivalent "bounce factor", q. For oblique impacts, the outgoing speed and spin of the ball also depends on the tangential coefficient of restitution, ex . Examples from baseball, tennis and other sports are highlighted.